Oral anticoagulant therapy related to oral surgery procedures - Knežević Milan; Petrović Dragan; Jović Nebojša; Bosch Carlos (Sanamed, 2011)
Today there must be established protocol in oral surgery treatment for the patients which are under anticoagulant treatment via oral (ATO). This is due to danger of the possible complications and also for increased demand for hospital treatment of these patients, which can be estimated now days as high as 8%. In the present study, the authors intent to define all the parameters for creation of one acting protocol applicable to this group of patients and concluding that there is no necessary need to suspend ATO previously to oral surgery procedures, moreover these procedures ought to be performed under interdisciplinary medical control.